Near-field directionality governed by asymmetric dipole-matter interactions - Zhong, Yuhan (2024)
Directionally molding the near-field and far-field radiation lies at the heart of nanophotonics and is crucial for applications such as on-chip information processing and chiral quantum networks. The most fundamental model for radiating structures is a dipolar source located inside homogeneous matter. However, the influence of matter on the directionality of dipolar radiation is oftentimes overlooked, especially for the near-field radiation. As background, the dipole-matter interaction is intrinsically asymmetric and does not fulfill the duality principle, originating from the inherent asymmetry of Maxwell's equations, i.e., electric charge and current density are ubiquitous but their magnetic counterparts are non-existent to elusive. We find that the asymmetric dipole-matter interaction could offer an enticing route to reshape the directionality of not only the near-field radiation but also the far-field radiation. As an example, both the near-field and far-field radiation directionality of the Huygens dipole (located close to a dielectric-metal interface) would be reversed if the dipolar position is changed from the dielectric region to the metal region.